Comparative analysis of the shrinkage stress of composite resins - Rosana Aparecida Pereira; Paulo Amarante de Araujo; Juan Carlos Castañeda-Espinosa; Rafael Francisco Lia Mondelli (University of São Paulo, 2008)
The aim of this study was to compare the shrinkage stress of composite resins by three methods. In the first method, composites were inserted between two stainless steel plates. One of the plates was connected to a 20 kgf load cell of a universal testing machine (EMIC-DL-500). In the second method, disk-shaped cavities were prepared in 2-mm-thick Teflon molds and filled with the different composites. Gaps between the composites and molds formed after polymerization were evaluated microscopically. In the third method, the wall-to-wall shrinkage stress of the resins that were placed in bovine dentin cavities was evaluated. The gaps were measured microscopically. Data were analyzed by one-way ANOVA and Tukey's test (alpha=0.05). The obtained contraction forces were: Grandio = 12.18 ± 0.428N; Filtek Z 250 = 11.80 ± 0.760N; Filtek Supreme = 11.80 ± 0.707 N; and Admira = 11.89 ± 0.647 N. The gaps obtained between composites and Teflon molds were: Filtek Z 250 = 0.51 ± 0.0357%; Filtek Supreme = 0.36 ± 0.0438%; Admira = 0.25 ± 0.0346% and Grandio = 0.16 ± 0.008%. The gaps obtained in wall-to-wall contraction were: Filtek Z 250 = 11.33 ± 2.160 µm; Filtek Supreme = 10.66 ± 1.211µm; Admira = 11.16 ± 2.041 µm and Grandio = 10.50 ± 1.224 µm. There were no significant differences among the composite resins obtained with the first (shrinkage stress generated during polymerization) and third method (wall-to-wall shrinkage). The composite resins obtained with the second method (Teflon method) differed significantly regarding gap formation.